The Blasé and the Flâneur. Simmel and Benjamin on Modern and Postmodern Forms of Individualization - Mele, Vincenzo (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2019)
Simmel’s blasé and Benjamin’s flâneur as symbols of their models of metropolitan subjectivity can be the necessary reference points for delineating two models, sometimes converging, other times diverging, regarding the representation of the individual and its possible autonomy in the context of the “aestheticization” of contemporary daily life. Simmel does not stop looking – albeit with an accent on the tragic that grew ever stronger in last stages of his reflections – at the individual and the process of individualization from the perspective of the ever more marked differentiation and growth of the vital possibilities of the individual. Simmel’s conception of life as Adventure expresses an irreversible trend of contemporary subjectivity, which is towards the realization of its peculiarity and uniqueness. Benjamin, on the contrary, criticizes the conception of the adventure as the very search for true “lived experience” (Erlebnis), because it would lead directly to the aestheticization of politics, the exaltation of the noble gesture, the search for the authentic − all the forms of cultural expression that led to fascism and war. He seems rather prefer going beyond − in the utopian and/or ideological sense − the individualistic structure of contemporary society. His hope was that the void created by the disappearance of the western individual could be filled by new forms and figures of subjectivity and intellectuality made possible through the means offered by the technical reproducibility of artwork. From an exquisitely theoretical point of view, nothing can guarantee a priori that the search for authenticity does not head in this regressive direction, instead of establishing a point of departure towards new ethical and political paths.